نقل الأعضاء من الموتى بين تحقيق حالة الوفاة والإنعاش الصناعي بين الفقه الإسلامي والقانون الوضعي - مراحى، ريم; جبيري، ياسين (جامعة الأمير عبد القادر للعلوم الإسلامية - كلية أصول الدين, 2022)
يعتبر تحديد لحظة الوفاة موضوعا مفصليا وحاسما في موضوع نقل وزراعة الأعضاء البشرية من الأموات إلى الأحياء، بحيث بدون الإقرار بوفاة الشخص في اللحظة المناسبة فاتت الفرصة والوقت المناسب الذي لا يزال فيه العضو يتمتع بمزاياه الحيوية لينقل إلى شخص يحتاجه، إن فكرة تحديد لحظة الوفاة لا تزال محل سجال ونقاش بين المختصين في الطب، والقانون ورجال الدين، فلابد من معيار فيصل كمرجع لتحديد الوفاة الحقيقية النهائية للشخص دون الخوض في حالة الغيبوبة وإمكانية الاعتداء على الشخص في حقه في الحياة، بإمكان رجوعه إلى الحياة مرة أخرى، أحاول في هذه الورقة البحثية تسليط الضوء على هذه الجزئية بالإجابة على الإشكال التالي: ما هو المعيار الحاسم في تحديد لحظة الوفاة؟ وهل لتقنيات ووسائل الإنعاش الصناعي أثر في ذلك؟ وهو ما سيتم تناوله في مبحثين رئيسيين: مبحث أول بعنوان معايير تحديد حالة الوفاة ونقل الأعضاء بين الطب والقانون والشريعة، ومبحث ثان: الإنعاش الصناعي ونقل الأعضاء بين الشريعة والقانون. Determining the moment of death is a detailed and decisive issue in the transfer and transplantation of human organs from the dead to the living, so that without acknowledging the death of the person at the right moment missed the opportunity and the right time when the member still has its vital advantages to convey to someone who needs it, the idea of determining the moment of death is still The subject of debate and debate between specialists in medicine, law and the clergy, it must be the Faisal standard as a reference to determine the final real death of the person without going into a state of coma and the possibility of assaulting the person in his right to life, can return to life again, I try in this paper shed Light on this partial answer to the following forms: What is the decisive criterion in determining the moment of death? Do the techniques and means of industrial resuscitation have an impact? This will be dealt with in two main topics: the first section entitled Criteria for determining the state of death and transfer of organs between medicine, law and Sharia, and a second topic: industrial resuscitation and organ transfer between Sharia and law.
Keywords: الأعضاء البشرية -- المسؤولية الجنائية -- الفقه الإسلامي -- القانون الوضعي -- الإحياء الإصطناعي